Pengujian Nilai Kekerasan Material ABS EH36 Hasil Proses Heat Straightening - Nurul Laili Arifin; Ikram Akrabi; Lalu Giat Juangsa Putra; Fedia Restu; Cahyo Budi Nugroho; Nugroho Pratomo Ariyanto (Jurnal Teknologi dan Riset Terapan (JATRA), 2023)
Heat straightening is a method of repairing material distortion caused by welding heat. Heat straightening is done by heating the material in an area that is distorted and cooled slowly in the air until the desired material dimensions tolerance appropriate are achieved. The Heat Straightening method is carried out at a range suhu 370â„ƒ-550â„ƒ using the oxy-acetylene method for the heating process. This research is aimed to find out effect Heat Straightening proses the hardness value on ABS EH36 material. The hardness testing method used is the Hardness Vickers test with load applied 10kgf on Carbon Steel ABS EH 36. From the research it is known that the hardness value in the base metal area is higher than the heat straightening area with an average hardness value of 192.1 HV10 in the base metal area and an average hardness value of 185 HV10 in the heat straightening area.